A bilevel hybrid economic approach for optimal deployment of onshore power supply in maritime ports. (15th June 2021) - Wang, Lifen; Liang, Chengji; Shi, Jian; Molavi, Anahita; Lim, Gino; Zhang, Yue
Highlights: A hybrid economic approach to increase uptake of onshore power supply and reduce at-berth emissions. A bilevel model that empowers the hierarchical decision-making process in the maritime industry. Simulation results reveal the environmental and economic advantages of the proposed approach. Abstract: Onshore power supply (OPS) is an effective measure to curb at-berth emissions by allowing berthed ships to switch off their auxiliary engines and plug into the shore-side electric grid for their power demand. Despite OPS's proven benefits in reducing emissions, port entities are often reluctant to adopt OPS technology due to the expensive electrical infrastructure retrofitting process. Hence, regulatory subsidies often play a key role in the promotion of OPS. This paper proposes a novel bilevel hybrid economic approach to jointly aid both the regulatory agency and the port entity to holistically increase OPS uptake. In the proposed model, the regulatory authority on the upper level acts first and develops the optimal hybrid incentive policy to minimize the negative environmental impacts caused by ships at berth. The port entity on the lower level then decides the most financially favorable and economically viable investment decisions regarding the selection and installation of OPS. The problem is formulated as a mixed-integer bilevel programming model and solved using a column and constraint generation method. The simulation-based case study shows the environmental and economic strength of the proposed hybrid economic approach compared to the conventional regulatory and market-based approaches.